2019
DOI: 10.3390/insects10020034
|View full text |Cite
|
Sign up to set email alerts
|

Limited Cross Plant Movement and Non-Crop Preferences Reduce the Efficiency of Honey Bees as Pollinators of Hybrid Carrot Seed Crops

Abstract: Pollination rates in hybrid carrot crops remain limited after introduction of honey bee hives. In this study, honey bee foraging behaviour was observed in commercial hybrid carrot seed crops. Significantly more visits were made to male-fertile (MF) rather than cytoplasmically male-sterile (CMS) flowers. Pollen was collected from bees returning to a hive, to determine daily variation in pollen loads collected and to what level the bees were foraging for carrot pollen. Honey bees visited a wide range of alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…In contrast, we found that both insects visited more hermaphrodite than female lines. Similar was found in other hybrid crops, such as carrots (Gaffney et al 2019), rapeseed mustard, sunflower and faba bean (Abrol 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, we found that both insects visited more hermaphrodite than female lines. Similar was found in other hybrid crops, such as carrots (Gaffney et al 2019), rapeseed mustard, sunflower and faba bean (Abrol 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies in hybrid seed crops have found that honeybees are not efficient pollinators (Abrol 2012;Gaffney et al 2019;Robinson 2019). Failure to set seed in hybrid crops has often been attributed to the poor attractiveness of female plants to honeybees that are foraging for pollen since they have no pollen reward (Parker 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In general, male sterile carrot flowers (not producing pollen) are the least visited [3], warranting the analysis of nectar as the likely most important reward. However, our analysis indicated that nectar composition varies greatly between umbellets within cultivars but not significantly among cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported species-selective pollinator visitation to hybrid carrot seed crops including pollinators such as A. mellifera [2,3,[6][7][8], flies [9,10], Megachile bees [11], and other native bees [12], but there appear to be no reports on carrot pollinator assemblage level visitation to different CMS cultivars, despite strong indications of differences in pollinator attraction among cultivars [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation